2018
DOI: 10.1186/s12936-018-2611-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and allele frequencies of Plasmodium falciparum msp1 and msp2 in parasite isolates from Bioko Island, Equatorial Guinea

Abstract: BackgroundMalaria is still a serious public health problem on Bioko Island (Equatorial Guinea), although the number of annual cases has been greatly reduced since 2004 through the Bioko Island Malaria Control Project (BIMCP). A better understanding of malaria parasite population diversity and transmission dynamics is critical for assessing the effectiveness of malaria control measures. The objective of this study is to investigate the genetic diversity of Plasmodium falciparum populations and multiplicity of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
50
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(74 citation statements)
references
References 31 publications
20
50
4
Order By: Relevance
“…Among the 320 patients evaluated on D3, 5.9% (19/320) showed D3 positivity by microscopy, which was also confirmed and identified the Plasmodium species by PCR-HRM (14,15). These 19 patients had D0 and D3 parasite densities of 900 to 8000 and 40 to 2120 parasites/μl, respectively.…”
Section: Resultsmentioning
confidence: 65%
See 4 more Smart Citations
“…Among the 320 patients evaluated on D3, 5.9% (19/320) showed D3 positivity by microscopy, which was also confirmed and identified the Plasmodium species by PCR-HRM (14,15). These 19 patients had D0 and D3 parasite densities of 900 to 8000 and 40 to 2120 parasites/μl, respectively.…”
Section: Resultsmentioning
confidence: 65%
“…Although DHA-PIP remains efficacious in the study region and those ART-resistance mutations are not found, ACT may pose positive selection on the parasites. In additionally, the rate of transmission and the diversity of vector species on Bioko Island may also increase selection pressure on parasite strains (14). More isolates from cases with delayed parasite clearance after DHA-PIP treatment indicated that in vitro and in viv o monitoring for ART derivatives and ACT partner drugs should be regularly performed on Bioko Island, Equatorial Guinea.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations